Induction Time Measurement of Barbital Tolerance in Mice Given Recurrent Subhypnotic Dosage of Barbital - Risher, Debra L. (1982)
A procedure designed to estimate the degree of development of neuronal tolerance to barbiturates is described. With this technique, it has been shown that a subhypnotic (125 mg/kg) peritoneal dose of barbital sodium, given twice daily, over the course of either five or 10 consecutive days, can produce significant elevation in tolerance over that found for analogous groups of saline control animals. Mean tolerances were considerably lower (about 20 percent) than those obtained when the recurrent barbital sodium dosages were at the hypnotic (300 mg/kg) level given once per day for 10 days. The results obtained support the proposition that the method employed is sufficiently sensitive to estimate neuronal tolerance developed as a result of recurrent administrations of subhypnotic dosages of barbiturates when given at adequate frequency and duration.